Yuval Noah Harari’s religious reflections = Religioznawcze refleksje Yuvala Noaha Harariego - Iwanicki, Juliusz (Przegla̜d religioznawczy, 2020)
The article aims to reconstruct and critically analyze the research of Yuval Noah Harari, an Israeli historian who devotes a lot of space to the categories of culture and religion in the study of global and macrohistorical processes. The author is a secularist researcher, quite clearly presenting materialistic and neo-evolutionary assumptions in his publications. The cultural studies phenomenon associated with this figure is the popularity of books and a video blog, run by a scholar from the Hebrew University.